(untitled) (Medico Legal Update, 2022)
Background: Premature Ejaculation is a common sexual disorder which negatively affects men’s life. Premature Ejaculation estimate prevalence is 20-30 %. It affects to overall quality of life and associated with anxiety, stress, and other psychological factors. Objective: The purpose of the study was to conduct a review of alternative therapy in the management of Premature ejaculation (PME). Method: A review was conducted using search terms Premature Ejaculation, Yoga Therapy, Alternative therapyand all the probable term in national and international data repositories such as PubMed, Scopus, science direct, google scholar, web of science in English language. Result: The review of alternative therapies in the management of Premature ejaculation suggests that most of the studies used Selective serotonin reuptake inhibitors (SSRIs), phosphodiesterase type 5 inhibitors (PDE5) and physical activity. There are very few studies conducted in relation to yoga and Premature ejaculation. Further, most of the studies explored effect of alternative therapies on psychological outcomes. Conclusion: Evidence suggests that Pharmacological clinical trial is effective with side effect, Cognitive behaviour therapy and Pharmacological Drugs separately both are less effective. One evidencebased study with integrated yoga therapy should be considered in the management of Premature ejaculation. Higherquality trial with yogic approach needed to first line management of patients presenting with Premature ejaculation.